Cobalt ferrite bearing nitrogen-doped reduced graphene oxide layers spatially separated with microporous carbon as efficient oxygen reduction electrocatalyst - Kashyap, V.; Singh, S. K.; Kurungot, S. (ACS Applied Materials and Interfaces, 2016)
The present work discloses how high-quality dispersion of fine particles of cobalt ferrite (CF) could be attained on nitrogen-doped reduced graphene oxide (CF/N-rGO) and how this material in association with a microporous carbon phase could deliver significantly enhanced activity toward electrochemical oxygen reduction reaction (ORR). Our study indicates that the microporous carbon phase plays a critical role in spatially separating the layers of CF/N-rGO and in creating a favorable atmosphere to ensure the seamless distribution of the reactants to the active sites located on CF/N-rGO. In terms of the ORR current density, the heat-treated hybrid catalyst at 150 °C (CF/N-rGO-150) is found to be clearly outperforming (7.4 ± 0.5 mA/cm 2 ) the state-of-the-art 20 wt % Pt-supported carbon catalyst (PtC) (5.4 ± 0.5 mA/cm 2 ). The mass activity and stability of CF-N-rGO-150 are distinctly superior to PtC even after 5000 electrochemical cycles. As a realistic system level exploration of the catalyst, testing of a primary zinc-air battery could be demonstrated using CF/N-rGO-150 as the cathode catalyst. The battery is giving a galvanostatic discharge time of 15 h at a discharge current density of 20 mA/cm 2 and a specific capacity of ∼630 mAh g -1 in 6 M KOH by using a Zn foil as the anode. Distinctly, the battery performance of this system is found to be superior to that of PtC in less concentrated KOH solution as the electrolyte.